Critical Review of Hingwashtaka Churna: A Polyherbal Ayurvedic Formulation - Sharma, Kulbhushan; Ruchika; Verma, Priyanka; Rao, K Shankar Rao (International Research Journal of Ayurveda & Yoga, 2024)
Hingwashtaka Churna is a polyherbal Ayurvedic formuluation first mentioned by Ashtanga Hridya in Gulma Chikitsa. Although it is not mentioned in Charak samhita and Sushruta Samhita, it is a very common, safe and easily available drug in the treatment of Mandagni related Vikara. It contains Hingu as main and a total number of eight ingredients along with Trikatu, Jeerakadvaya, Saindhava Lavana and Ajawain. This study critically analyzes various references of the polyherbal formulation for the appropriate way of preparation and the samprapti vighatan which Hingwashtaka Churna ensures in treatment of Vataj Gulma, Vataroga, Agnimandya, Shoola etc.